2021
DOI: 10.3390/ijerph182010944
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Perceived Design Intensity, Preference, Restorativeness and Eye Movements in Designed Urban Green Space

Abstract: Recent research has demonstrated that landscape design intensity impacts individuals’ landscape preferences, which may influence their eye movement. Due to the close relationship between restorativeness and landscape preference, we further explore the relationships between design intensity, preference, restorativeness and eye movements. Specifically, using manipulated images as stimuli for 200 students as participants, the effect of urban green space (UGS) design intensity on landscapes’ preference, restorativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Therefore, this study attempted to explore objective gender differences from a visual perspective, assuming that different visual behaviors result in different experiences between men and women. Wu et al (2021) [27] pointed out that eye-movement indicators are likely to be predictors of landscape preference. A study by Li et al (2020) [28] revealed the importance of landscape elements decomposition for visual perception and evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study attempted to explore objective gender differences from a visual perspective, assuming that different visual behaviors result in different experiences between men and women. Wu et al (2021) [27] pointed out that eye-movement indicators are likely to be predictors of landscape preference. A study by Li et al (2020) [28] revealed the importance of landscape elements decomposition for visual perception and evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Eye-tracking technology provided effective data to test this hypothesis. Eye trackers can accurately record respondents' eye-movement trajectories when observing a scene and generate large amounts of data to analyze observation patterns and focus [27,29]. Multiple studies have used eye tracking to investigate group differences in landscape perception, often examining variables such as expertise, gender, and cultural background [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigating the relationship between landscapes and perceived restorativeness have used psychological questionnaires [36,37]. However, some scholars have employed physiological measurement techniques such as heart rate variability (HRV) [38], blood pressure (BP) [39], skin conductance response (SCR) [3], electroencephalography (EEG) [40], and eye-tracking [41] to more scientifically and objectively verify the relationship between landscapes and perceived restorativeness. Among these measures, EEG most effectively reflects the degree of stimulation experienced by individuals, thus indicating their emotional changes in different landscape settings [42].…”
Section: Objective and Reliable Measurement Toolsmentioning
confidence: 99%
“…In this study, photographs were used to represent each rural landscape type. Multiple studies have confirmed that photographs can effectively substitute for on-site environmental surveys [3,41,60]. The selection of images for the experiment was completed through focus group interviews and expert evaluations [61].…”
Section: Selection Of Experimental Imagesmentioning
confidence: 99%
“…Meanwhile, Wu et al examined the effects of urban green space (UGS) design intensity on landscape preference, restorativeness, and eye movement, using treatment images with 200 students as participants. The most feasible regression equations between design intensity and preference, restorativeness, and eye movement were obtained [46]. In addition, Ding et al used eyetracking technology to study the extent of people's preference for native greenery plants from the perspective of visual preference using pictures of plant organs such as leaves, flowers, and fruits as stimulating materials to improve rural greening techniques, with a study conducted by students from the Central South University of Forestry Technology and villagers in Changkou Village, Fujian Province [47].…”
Section: Landscape Preference Theory and Eye-tracking Technologymentioning
confidence: 99%